"No Cult Tells You to Think for Yourself": Discursive Ideology and the Limits of Rationality in Conspiracy Theory QAnon. (May 2023) - Forberg, Peter L.
What is truth in politics? Movements such as the anti-establishment, internet-born conspiracy theory QAnon are offered as dramatic cases of just how "irrational" people have become in a "post-truth" political world. However, with a growing number of everyday Americans believing in such theories, labeling adherents "irrational" ignores the internally rationalizing logic of conspiracy theories, so we ask the question: how do QAnon followers think through, argue, and rationalize their political truths? This paper establishes a discursive framework that demonstrates how QAnon adherents translate the theory's paradigmatic political epistemology into personal ideologies. I identify the narrative structures that guide belief, examining how QAnon followers develop a general political plot, set the parameters for conflict, embrace their role in the story, determine what is in the political canon, and relate to the narrative that has been constructed. This analysis highlights the contradictions within the QAnon conspiracy theory—not to pathologize adherents' irrationality but to demonstrate how people must wrestle with contradiction, paradox, and confusion when developing political ideologies. When framed as the as victims of a brainwashing cult, QAnons routinely respond, "no cult tells you to think for yourself"; instead, their narratives allow them to interpret QAnon in service of developing personalized political truths. Thus, this paper takes their words at face value to see the world as they interpret it. I argue that ideologies are a function of broader political epistemologies such as QAnon; they are embodied, narrativized ways of being in the world that make life livable—despite any inner contradictions—and guide political participation.